INFERENCES ON THE GEOMETRY OF THE NAZCA PLATE IN NORTHWESTERN PERÚ BASED ON DATA COLLECTED BY A LOCAL SEISMOGRAPH NETWORK - Tavera Hernando; Vilca Renzo; Marín Gloria (Earth Sciences Research Journal)
In Central and Southern Peru, local and teleseismic data allow having insights on the Wadati-Benioff zone (WBZ) geometry. In the region of Northern Perú, only rough estimates of the WBZ geometry have beenproposed, and were obtained using teleseismic data due to the reduced number of mb≥4.0-magnitude earthquakes available. The installation of a local seismic network in the NW border of Northern Perú, allowedthe recording of a large number of earthquakes with magnitudes ranging from 1.8 to 4.1 ML, and maximum depths of 120 km., distributed over the area where the occurrence of earthquakes with magnitudes > 4.0 isscarce. In a vertical section, oriented N70˚E earthquakes are distributed along a 10° dipping plane from the trench. Landwards from the coastline, the dip angle increases to 28°. These results allow a high resolutiondefinition of the Nazca plate geometry in NW Perú. Focal mechanisms computed for 22 earthquakes located between 50 and 120 km depth beneath the network suggest the development of deformation processes in direction parallel to the convergence Nazca plate direction.